The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1128/aac.37.9.1873
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations in plasma and tissue penetration of ceftriaxone and ornidazole during liver transplantation

Abstract: Plasma and epiploic fat drug concentrations and fat penetration of ceftriaxone and ornidazole given for antimicrobial prophylaxis were studied in 11 patients scheduled for liver transplantation. Ceftriaxone (1 g) and ornidazole (500 mg) were infused during 30 min after the induction of anesthesia. Arterial blood and epiploic fat samples were collected at 30, 60, and 120 min and then every 90 min following the end of the infusion until closure of the peritoneum. Blood samples were immediately centrifuged, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Bioanalytical methods for the quantification of ceftriaxone in plasma, urine, fat tissue, bones or cerebrospinal fluid with application in in vivo studies were available (Bowman et al, 1984;Gergs et al, 2014;Kratzer et al, 2014;Mcwhinney et al, 2010;Page-Sharp et al, 2016;Payasi et al, 2010;Ringger et al, 1996Ringger et al, , 1998Schleibinger et al, 2015;Steib et al, 1993;Sun et al, 2012;Verdier et al, 2011). High performance liquid chromatography (HPLC) systems with different detectors were used.…”
Section: Introductionmentioning
confidence: 99%
“…Bioanalytical methods for the quantification of ceftriaxone in plasma, urine, fat tissue, bones or cerebrospinal fluid with application in in vivo studies were available (Bowman et al, 1984;Gergs et al, 2014;Kratzer et al, 2014;Mcwhinney et al, 2010;Page-Sharp et al, 2016;Payasi et al, 2010;Ringger et al, 1996Ringger et al, , 1998Schleibinger et al, 2015;Steib et al, 1993;Sun et al, 2012;Verdier et al, 2011). High performance liquid chromatography (HPLC) systems with different detectors were used.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies in a larger cohort are indicated to explore the true significance of these results. While it could explain our results, whether the pharmacodynamics of intravenous ceftriaxone are such that the peritoneal drug concentration following a 1 g infusion results in slower control of infection is unclear from our study 19 . Third, the number, duration and complexity of antibiotic regimens that cirrhotic patients experience is highly variable.…”
Section: Discussionmentioning
confidence: 74%
“…The activity of 8 anti-Mab drugs, 9 nitro-compounds and colistin (CLS) was tested against A and H cells. The list of drugs is shown in Supplementary Table S2 [ 21 , 22 , 25 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The drugs were purchased from Sigma-Aldrich (St. Louis, MO, USA) or Selleck Chemicals (Houston, TX, USA).…”
Section: Methodsmentioning
confidence: 99%